2011
DOI: 10.2355/isijinternational.51.945
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach to Modeling the Flow Curve of Hot Deformed Austenite

Abstract: A new, more physically realistic and practically useful model is presented for the simulation of high temperature austenite flow curves. It is an extension of our earlier empirical model based on the Avrami kinetics of dynamic recrystallization. In the new approach, the normalization parameter is expressed in terms of the fractional recrystallization and not the amount of softening. Compression experiments carried out on a Nb-modified plain carbon steel enable the simulated flow curves and progress of recrysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 17 publications
2
19
0
Order By: Relevance
“…(1). 15) This rule of mixtures is based on the current values of the work hardening flow stress σwh pertaining to the unrecrystallized material and the dynamic recrystallization flow stress , which represents the average flow stress of the material that has already undergone dynamic recrystallization. Here X is the fractional softening due to DRX, which can be defined as X=(σwh -σ)/(σwh -).…”
Section: General Equation Describing the Flow Curvesmentioning
confidence: 99%
See 3 more Smart Citations
“…(1). 15) This rule of mixtures is based on the current values of the work hardening flow stress σwh pertaining to the unrecrystallized material and the dynamic recrystallization flow stress , which represents the average flow stress of the material that has already undergone dynamic recrystallization. Here X is the fractional softening due to DRX, which can be defined as X=(σwh -σ)/(σwh -).…”
Section: General Equation Describing the Flow Curvesmentioning
confidence: 99%
“…In this relation, the saturation stress σsat in Eq. (3) is replaced by the critical stress σc, the stress value for the initiation of DRX, which has previously been demonstrated to be equal to the steady state stress σss; 15) it can be considered as the average stress when all the grains have undergone at least one cycle of DRX. The work hardening parameter r', is introduced to take into account the average recovery rate of the crystals that are currently at different stages of DRX in the recrystallized portion of the material.…”
Section: The Work Hardening Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, both the Avrami exponent and the time required to achieve 50% DRX are determined from the work-softening transients present in some of the stress-strain curves. However, the model can be simplified on the ba-M a n u s c r i p t sis of the experimental results reported by Jonas et al (2009) and Quelennec et al (2011), who demonstrated that, for a broad range of steel grades, the steady state stress is equal to the critical stress for the nucleation of DRX.…”
Section: Description Of the Constitutive Modelmentioning
confidence: 99%